Coupling 2-Aminopurine with DNA Copper Nanoparticles as a Rapid and Enzyme-Free System for Operating DNA Contrary Logic Pairs - Jun Wang; Jiawen Han; Xujuan Lv; Jingyu Hou; Daoqing Fan; Shaojun Dong (Chemistry, 2023)
Exploring affordable and efficient platform for innovative DNA computing is of great significance. Herein, by coupling 2-aminopurine (2AP) with DNA copper nanoparticles (CuNPs) as two universal opposite outputs, we, for the first time, fabricated a rapid and enzyme-free system for operating DNA contrary logic pairs (D-CLPs). Notably, derived from the rapid and concomitant response of both fluorescent probes, different D-CLPs can be achieved via a “double-results-half-efforts” manner in less than 20 min with low-cost. Moreover, based on the same system, the smart ratiometric analysis of target DNA was realized by employing the high reliability and accuracy of D-CLPs, providing a robust and typical paradigm for the exploration of smart nucleic acid sensors.